Study on Total Phenolic Content (TPC), Total Flavonoid Content (TFC), and Antioxidant Activities of Urtica dioica of Nepalese Origin - Bhatt, Bishan Datt; Parajuli, Gagan Chandra (Journal of Nepal Chemical Society, 2017)
Available with full text